Consciência fonológica no processo de aquisição da leitura e da escrita - Almeida, Graciliana Ribeiro de (2018)
The present study has as object of study the phonological awareness and the difficulties inherent to the acquisition of reading and writing within the Literacy Cycle, period that includes part of the age group of childhood, on average children from 6 to 8 years of age. This cycle covers the 1st to 3rd year of elementary school. The study describes the investigation of the deviations found in the textual productions of students of the 2nd year of elementary school I, and the recurrent deviations in the writing of the texts taken for analysis in this research refer to the nonconventional segmentation, for which we apply a proposal of activities based on phonological awareness, aiming to soften the problems identified during the investigation. According to Costa (2012, p.16), "phonological awareness is in the context of linguistic consciousness and is the human capacity to reflect and manipulate phonological units (syllables, intra-syllabic units and phonemes)". Thus, the objectives of this study are: a) to identify the recurrent deviations in the students' textual productions; b) select the phonological-phonological processes that will be worked following the proposed activities; c) to elaborate and apply a sequence of activities built from the perspective of phonological awareness, seeking to treat the identified and selected deviations in the textual productions of the students of the 2nd year of Elementary School I; d) analyze the reading and writing practices of the students, after the implementation of the sequence of activities. In the analysis of textual productions, the cases of more recurrent deviations were related to nonconventional segmentation - hyposegmentation and hypersegmentation, these being the privileged processes in the didactic intervention proposal covered in this research. The results obtained in this study show that in the Literacy Cycle the student still does not recognize the graphic limits of words, thus tending to join or separate the word outside the orthographic conventions of Brazilian Portuguese.